CAMKKβ supports growth and viability of epithelial ovarian cancer in vitro and in vivo - Matthew J. Borrelli; Adrian Buensuceso; Yudith Ramos Valdes; Tiffany P.A. Johnston; Jacob Haagsma; Trevor G. Shepherd (Scientific Reports)
Abstract Epithelial ovarian cancer (EOC) metastasizes predominantly through multicellular aggregates known as spheroids, which disseminate within the peritoneal cavity and initiate secondary disease upon reattachment at distant sites. EOC spheroids resist detachment-induced cell death by upregulating stress responses including AMP-activated protein kinase (AMPK) signaling and AMPK-dependent macroautophagy (autophagy), highlighting these pathways as potential therapeutic targets. Previously, we used a pharmacological approach to putatively identify Ca2+/calmodulin-dependent protein kinase kinase 2 (CAMKKβ, encoded by CAMKK2) as the primary activator of AMPK in EOC spheroids. Herein we have generated CAMKK2 knockout EOC cell lines via CRISPR–Cas9 genome editing to confirm this function of CAMKKβ and explore the impacts of its loss using in vitro and in vivo models of metastatic EOC. CAMKK2 knockout spheroids exhibited decreased AMPK activation, autophagic flux, cell viability, and metastatic potential relative to parental spheroids, and intraperitoneal xenograft tumours lacking CAMKKβ grew slower than their CAMKKβ-intact counterparts. Effect magnitudes varied between cell line models, suggesting context-dependent roles for CAMKKβ in EOC and rationalizing further studies to characterize the underlying mechanisms. Altogether, our findings highlight CAMKKβ as an important contributor to metabolic reprogramming in EOC spheroids and as a potential therapeutic target in the setting of advanced disease.